Microbiologically-Influenced Corrosion of 1020 Carbon Steel in Artificial Seawater Using Garlic Oil as Natural Biocide - Silva,Priscila Santos da (2019)
This work aims evaluate the use of biocides in the microbiologically-influenced corrosion (MIC) of AISI 1020 carbon steel by sulfate-reducing bacteria (SRB) in artificial seawater. A natural biocide (garlic oil) and a commercial biocide (glutaraldehyde) were used to control the corrosion caused by these bacteria in artificial seawater. Microbial growth on the steel surface was evaluated by quantifying the sessile SRB using the most probable number (MPN) method. The action of biocides in the biocorrosion process was studied by electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization. The biofilm formation and the corrosion products on the steel surface were observed by scanning electron microscopy (SEM). The results showed that, although it was not able to inhibit the growth of sessile SRB completely, garlic oil showed a greater reduction in the corrosion process when compared to glutaraldehyde, indicating its possible application as a natural biocide under these conditions.